High remanance of strontium hexaferrite from millscale derived / N. M. Saiden … [et al.] - N. M., Saiden; H., Azhan; M., Hashim; N., Yahya; R. S., Azis; E.A., Othman (Universiti Teknologi MARA Cawangan Pahang, 2005)
Strontium hexaferrite was prepared by using millscale as raw materials. Millscale is an impure iron oxide. The mil/scale was milled to obtain < 20um size powder particle in diameter and the oxide powder was separated into magnetic and non-magnetic particle in a I tesla external field. Magnetic particles such as magnetite (Fe3O4) were separate and wuestite (FeO) was oxidised into hematite (Fe2O3) at 500°C for 10 hours in air. The conventional sintering method was used for preparing green powder of strontium ferrite with composition SrO.6Fe2O3 r This process was done by utilising dry method in the mixing of Fe2O3 and SrCO3. The final sample was in pallet shape with 10.84 mm diameter width and 11.39mm tickness. The sample was magnetized, followed by measurement of remanance, coercive force and (BH) of strontium ferrite permanent magnet. Resistivity, curie temperature and density of sample were also measured. The results showed that mill scale has the potential to be a raw material for a high quality permanent magnet material in the future.